2015
DOI: 10.1111/bph.13056
|View full text |Cite
|
Sign up to set email alerts
|

Renal effects of chronic pharmacological manipulation of CB2 receptors in rats with diet‐induced obesity

Abstract: BACKGROUND AND PURPOSEIn diabetic nephropathy agonism of CB2 receptors reduces albuminuria and podocyte loss; however, the role of CB 2 receptors in obesity-related nephropathy is unknown. The aim of this study was to determine the role of CB 2 receptors in a model of diet-induced obesity (DIO) and characterize the hallmark signs of renal damage in response to agonism (AM1241) and antagonism (AM630) of CB2 receptors. EXPERIMENTAL APPROACHMale Sprague Dawley rats were fed a high-fat diet (HFD: 40% digestible en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 74 publications
7
44
0
Order By: Relevance
“…Aligning well with the above review, also within this issue is an original contribution from Jenkin et al (2016) that focuses on the role of CB 2 receptors in obesity-induced renal dysfunction. Using a high fat diet-induced rat model of obesity, they studied the effects of both activation (with AM1241) and blockade (with AM630) of the CB 2 receptor.…”
supporting
confidence: 53%
“…Aligning well with the above review, also within this issue is an original contribution from Jenkin et al (2016) that focuses on the role of CB 2 receptors in obesity-induced renal dysfunction. Using a high fat diet-induced rat model of obesity, they studied the effects of both activation (with AM1241) and blockade (with AM630) of the CB 2 receptor.…”
supporting
confidence: 53%
“…The CB1 receptors are expressed in high abundance with a fairly broad localization pattern, which includes all segments of the nephron and vasculature (Hryciw and McAinch, 2016). On the other hand, the CB2 receptor has been primarily detected in the renal cortex, specifically in mesangial cells and podocytes in the glomerulus (Deutsch et al, 1997;Barutta et al, 2011), and in proximal tubular epithelial cells (Jenkin et al, 2010(Jenkin et al, , 2013(Jenkin et al, , 2016. The CB2 receptor is an attractive pharmaceutical target owing to the lack of psychotropic effects associated with CB1 receptor activation (Mukhopadhyay et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Mice injected with the CB2R antagonist SR144528 for 4 weeks displayed a slight nonsignificant increase in body weight (24). In contrast, Jenkin et al reported that treatment with the CB2R agonist AM1241 or antagonist AM630 did not reduce weight gain or food consumption in diet-induced obese rodents (23). Using knockout models, Schmitz et al reported age-dependent proinflammatory obesity and visceral hypertrophy in CB2R-deficient mice on a standard diet compared with WT mice (26), a conclusion consistent with our findings of slightly higher body weight of CB2 −/− mice at baseline as well as after 12 weeks of LFD.…”
Section: Discussionmentioning
confidence: 99%